Simulation of electrical faults of three phase induction motor drive system - Muhammad Alif, Mohd Nor (2009)
The title of this project is Simulation of electrical faults of three phase induction motor drive system. Induction motor or asynchronous motor is a type of alternating current motor where power is supplied to the rotor by means of electromagnetic induction. Induction motor is now the preferred choice for industrial motor due to their rugged construction, absence of brushes (which are required in most DC motors) and the ability to control the speed of motor. The faults that can occur in the three-phase induction motor and its driver can be divided into two parts; internal and external faults. The internal fault of induction motors account for the proportion almost more than 70% of induction motor failures. This project will cover and study a few type of internal and external faults, which is the stator inter-turn short circuit, unbalanced voltage supply and the single phase open circuit fault. The study of induction motor is crucial and important so that the lifespan of the motor can be prolonged. In this project MATLAB SIMULINK is used to simulate the induction motor faults and analyze the condition. The simulation file is then compiled along with a GUI to simplify the overall process and improves the user friendliness to users.